Preliminary evidence for differential effects of integral and incidental emotions on risk perception and behavioral intentions: A meta‐analysis of eight experiments. (18th September 2020) - Ferrer, Rebecca A.; Ellis, Erin M.
Abstract: Judgment and decision‐making research often examines effects of emotion unrelated (i.e., incidental) to the decision when research questions center on emotion related (i.e., integral) to the decision, with a theory‐based assumption that the two types of emotion have equivalent influence. Experimentally targeting incidental emotion can overcome practical and ethical challenges that preclude manipulating integral emotion, particularly in medical contexts; however, the validity of the assumption that integral and incidental emotions have interchangeable influences on judgments and decisions, such as risk perceptions and behavioral intentions, has not been systematically examined. In a pre‐registered meta‐analysis of eight experiments ( n = 5, 336), we examined whether incidental fear and anger influenced risk perceptions and intentions similarly to integral fear and anger. To ensure the quality and intensity of the emotional experience remained constant across conditions, we rendered emotion integral or incidental to the threat by varying the type of outcomes assessed (matched or unmatched to the emotion induction). Results provide preliminary evidence that integral and incidental influences can differ. Most notably, incidental anger decreased risk perceptions, whereas integral anger increased them. Moreover, even when the direction of the effect of integral and incidental emotions was similar, the magnitude of the integral effect was larger. These findings suggest that the common practice of manipulating incidental emotions and generalizing findings to integral emotions may not be advisable, and as such, future work is needed to identify the specific features of the incidental and integral emotional experience that contribute to similarities and differences in their influence.